Simultaneous early surgical repair of post-cholecystectomy major bile duct injury and complex abdominal evisceration: A case report. (May 2022) - Torretta, Alfredo; Kaludova, Dimana; Roy, Mayank; Bhattacharya, Satya; Valente, Roberto
Abstract: Background: Major bile duct injuries (BDIs) are hazardous complications during 0.4%–0.6% of laparoscopic cholecystectomies. Major BDIs usually require surgical repair, ideally either immediately or at least six weeks after the damage. The complexity of our case lies in the coexistence of early BDI followed by 2-week biliary peritonitis with massive midline evisceration which, in combination, has over 40% mortality risk. Methods & case report: We describe the case of a 65-year-old male, transferred to our tertiary HPB service on day 14 after common bile duct complete transection during cholecystectomy and postoperative laparotomy. The patient presented with biliary peritonitis along with full wound dehiscence and extensive evisceration. During emergency peritoneal wash-out surgery we deemed immediate BDI repair feasible by primary Roux-en-Y hepaticojejunostomy (HJ), with multi-stage abdominal closure. In the following days we performed progressive abdominal wall closure in multiple sessions under general anesthesia, aided by vacuum-assisted wound closure and intraperitoneal mesh-mediated fascial traction-approximation (VAWCM) with permeable mesh. An expected late incisional hernia was eventually repaired through component separation and biological mesh. Discussion & conclusion: The simultaneous use of Roux-en-Y HJ and VAWCM has proven safe and effective in the treatment of BDI and 2-week biliary peritonitis with massive midline evisceration. Highlights: Bile Duct Injuries (BDIs) are hazardous complications associated to 0.4%-0.6% laparoscopic cholecystectomies. Major BDIs usually require surgery, ideally either immediately or at least six weeks after index surgery. In this case a major BDI was associated with biliary peritonitis and abdominal evisceration, making high risk operative management necessary. Primary Roux-en-Y hepaticojejunostomy combined with contemporary management of the defect of abdominal wall with VAWCM has proven safe and successful.